Pengaruh Komik Makanan Sehat terhadap Pengetahuan Makanan Sehat pada Anak Usia Dini - Carissa Izza Shafa; Ferry Darmawan; Arif Hakim (UNISBA Press, 2022)
Abstract. Healthy food is a major factor in the growth and development of early childhood, the nutrients in food affect the health and intelligence of children. Through the educational process provided in schools, children are able to form understanding and knowledge about healthy food. In Early Childhood Education learning activities cannot be separated from the use of learning media, one of which is the use of visual media. One of the visual communication media that is interesting for early childhood is comics. This comic media was developed into a book, namely Healthy Food Comics. The subjects in this study were 15 children aged 5-6 years. With a pre-experimental research design with an analytical design of